An Odyssey: A Father, a Son, and an Epic - Daniel Mendelsohn
When eighty-one-year-old Jay Mendelsohn decides to enroll in the undergraduate Odyssey seminar his son teaches at Bard College, the two find themselves on an adventure as profoundly emotional as it is intellectual. For Jay, a retired research scientist this return to the classroom is his "one last chance" to learn the great literature he'd neglected in his youth--and, even more, a final opportunity to more fully understand his son, a writer and classicist. But through the sometimes uncomfortable months that the two men explore Homer's great work together--first in the classroom, where Jay persistently challenges his son's interpretations, and then during a surprise-filled Mediterranean journey retracing Odysseus's famous voyages--it becomes clear that Daniel has much to learn, too: Jay's responses to both the text and the travels gradually uncover long-buried secrets that allow the son to understand his difficult father at last.